Perkembangan Pandai Besi Di Nagari Sungai Pua (1998-2020) - Afrizal Afrizal; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2023)
This research examines the Development of Blacksmiths in Nagari Sungai Pua (1998-2020). The problem is formulated as follows: